Plasmalogens Mediate the Effect of Age on Bronchodilator Response in Individuals With Asthma - Sordillo, Joanne E.; Lutz, Sharon M.; Kelly, Rachel S.; McGeachie, Michael J.; Dahlin, Amber; Tantisira, Kelan; Clish, Clary; Lasky-Su, Jessica; Wu, Ann Chen (Frontiers in Medicine, 2020)
Background: Asthma is known to display different phenotypes across the life-course, suggesting that age related changes are particularly relevant to understanding asthma pathogenesis and remission. We have previously demonstrated that a lung function phenotype associated with asthma, bronchodilator response, is reduced with age, at rate of approximately 0.3 percent per year. Methods: In this study, we interrogated the serum metabolome, to determine whether circulating metabolites mediate age-related changes in bronchodilator response (BDR) for individuals with asthma. We used data on 295 participants from the follow-up phase of the CAMP clinical trial (age 12.2 to 29.5 years; mean BDR of 8%, standard deviation 7%). Using a counterfactual framework, we analyzed over 500 pareto-scaled metabolites using mediation analysis to identify indirect effects of age through potential metabolite mediators. Results: There was a significant indirect effect of age on BDR through 4 plasmalogens (C36:1 PC and related metabolites) (Indirect Effect Beta= -0.001, p=0.006). Conclusions: Our findings suggest that plasmalogens may contribute to age-related asthma phenotypes, and may also serve as potential pharmacologic targets for enhancement of lung function in individuals with asthma.